2022
DOI: 10.1029/2022jd037218
|View full text |Cite
|
Sign up to set email alerts
|

The Persistence and Reemergence of Atmospheric Anomaly Signals in Soil Temperature

Abstract: Land surface is one of the important components of the earth climate system, and soil temperature (ST) is a key factor of land surface processes. As an indicator of heat storage in land surface, ST plays an important role in land-atmosphere interactions. The anomalies in ST can change surface sensible flux, latent flux, longwave radiation, etc., and further affect weather and climate on multiple time scales (Q. Hu & Feng, 2004;Mahanama et al., 2008;Wu & Zhang, 2014). Moreover, ST can change the locations and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A change in soil temperature might alter the physical properties of soil, which could then impart substantial impact on the physical, chemical, and biological processes occurring both above and below ground (Davidson and Janssens., 2006;Giardina et al, 2014;Hartley., 2014;Zhang et al, 2016;Li et al, 2022). Understanding the variations of soil temperature is of Frontiers in Environmental Science frontiersin.org great importance for assessing energy exchange between the soil and the atmosphere in relation to climate change (Du et al, 2017;Shen et al, 2020;Liu et al, 2022;Oogathoo et al, 2022;Song et al, 2022). This study found a significant seasonal pattern contrary to the variation of average shallow and deep soil temperature, i.e., it decreases (increases) with increasing soil depth in spring and summer (autumn and winter) at 00:00-23:00.…”
Section: Change Trendmentioning
confidence: 73%
See 1 more Smart Citation
“…A change in soil temperature might alter the physical properties of soil, which could then impart substantial impact on the physical, chemical, and biological processes occurring both above and below ground (Davidson and Janssens., 2006;Giardina et al, 2014;Hartley., 2014;Zhang et al, 2016;Li et al, 2022). Understanding the variations of soil temperature is of Frontiers in Environmental Science frontiersin.org great importance for assessing energy exchange between the soil and the atmosphere in relation to climate change (Du et al, 2017;Shen et al, 2020;Liu et al, 2022;Oogathoo et al, 2022;Song et al, 2022). This study found a significant seasonal pattern contrary to the variation of average shallow and deep soil temperature, i.e., it decreases (increases) with increasing soil depth in spring and summer (autumn and winter) at 00:00-23:00.…”
Section: Change Trendmentioning
confidence: 73%
“…Meanwhile, as important thermal and hydrological factors of the ground at any given location, soil temperature and soil moisture respond quickly to the effects of climate change and interact with the overlying atmosphere through the surface energy, water balance, and carbon cycles, substantially promoting feedback to regional climate (Albergel et al, 2015;Zhu et al, 2021;Liu et al, 2022). Soil temperature is also an important indicator of climate change and a critical parameter in numerical weather forecasting and climate prediction (Holmes et al, 2008;Qian et al, 2011;Albergel et al, 2015;Li et al, 2022;Song et al, 2022). It is currently unknown whether global soil temperatures experienced the same hiatus in rise as that shown in global air temperatures in the early 21st century (Wang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The anomalies of antecedent ST can persist in the shallow soil, and then affect current ST in the shallow soil (Song et al, 2022a(Song et al, , 2022b. Moreover, the anomalies of antecedent ST can propagate downwards, mainly persist in the middle and deep soil, propagate upwards in soil under suitable conditions (Matsumura & Yamazaki, 2012;Schaefer et al, 2007;Song et al, 2022aSong et al, , 2022b, and then affect current ST in the shallow soil (Figure 7a). Both processes can also be deduced based on the studies of Kolstad et al (2017).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…As shown in Equation 19and Figure 7a, the anomalies of antecedent ST can lead to the anomalies of current ST by the persistence of anomaly signals in soil, which implies the correlations between antecedent and current STs. The anomalies of antecedent ST can persist in the shallow soil, and then affect current ST in the shallow soil (Song et al, 2022a(Song et al, , 2022b. Moreover, the anomalies of antecedent ST can propagate downwards, mainly persist in the middle and deep soil, propagate upwards in soil under suitable conditions (Matsumura & Yamazaki, 2012;Schaefer et al, 2007;Song et al, 2022aSong et al, , 2022b, and then affect current ST in the shallow soil (Figure 7a).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A further increase in soil temperature in tropical regions would lead to more negative effects, including seedling death, smaller plants, higher water needs, and increased vulnerability to different plant diseases [7]. At the same time, since soil temperature records can be used to investigate the link between meteorological factors [8], soil temperature often plays a crucial role in numerical weather prediction and is a crucial indicator of climate change patterns [9][10][11][12]. Therefore, monitoring and predicting soil temperature can greatly support the development of sustainable agriculture by providing insights into soil health for seed germination, fruiting, flowering, and the growth of crop species.…”
Section: Introductionmentioning
confidence: 99%